PREPARATION OF ACTIVATED CARBON FROM TIRE DERIVED PYROLYTIC CHAR FOR ADSORPTION OF TETRACYCLINE HYDROCHLORIDE - Khulanuttha Chana; Sasit Soisuwan; Sarawut Sinpichai; Bing-Hung Chen; Duangkamol Na-Ranong (My University, 2022)
Effects of activation variables on performance of the obtained activated carbon (AC) were investigated for removal of tetracycline hydrochloride (TCH). Pyrolytic char derived from waste tire was chemically activated via two-step of KOH impregnation following by thermal treatment. According to regression analysis and fitting with second-degree polynomial equation, empirical models were developed to correlate performance of AC in TCH adsorption (percentage removal and adsorption capacity at equilibrium) with three activation variables: impregnation ratio (IR), activation temperature (T) and holding time of thermal treatment (t). The analysis of variance indicated that only T, T2 and IR2 were significant to the prediction of both percentage removal and adsorption capacity. According to the developed models, it is suggested that the pyrolytic char should be activated at IR = 6, T = 750 °C and t = 2 h to obtain the highest efficiency of TCH removal in the tested range of activation condition.
Keywords: Pyrolytic carbon; Tetracycline Hydrochloride; Adsorption and biosorption for pollutant removal